Explanation of Akidah in the Works of Patani Ulama and its Relation to Method of Aqidah Hurairan By Imam Al-Nawawi - Abdulhadee Sabuding (International Journal of Nusantara Islam, 2014)
This article discuss about method of explanation of akidah in the work of patani ulama and and method of explanantion of imam al-Nawawi about akidah and recognizing clearlly similarities of method of explanation of ulama patani with imam al-Nawawi. The article is qualitative study using library risearch and analytical data in the form of descriftive with two principle of deductive an inductive. Researh findings show that method of al-nawawi in explaining aqidah is a combination of Salaf and Khalaf, but patani ulama use rather the khalaf method. This study also shows that there is a similar method between the two different ulama in dealing with explanation of aqidah. However, there are also points of different between them in the way they use Salaf and khalaf. Imam al_Nawawi uses Salaf method for the first following by Khalaf on the contrary the Patani Ulama applied Khalaf as starting point followed by Salaf.